2019
DOI: 10.3382/ps/pez254
|View full text |Cite
|
Sign up to set email alerts
|

The effects of varieties and levels of rapeseed expeller cake on egg production performance, egg quality, nutrient digestibility, and duodenum morphology in laying hens

Abstract: The objective of this study was to evaluate the effects of rapeseed expeller cake (REC) derived from Brassica napus rapeseed with different concentrations of glucosinolate (Gls) and erucic acid (EA) on the egg-production performance, egg quality, apparent nutrient digestibility, and intestinal morphology in laying hens. At 33 wk of age, a total of 1,080 laying hens were randomly divided into 9 treatment groups in a completely randomized design involving a control treatment without REC (a corn–soybean diet) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 44 publications
2
16
0
5
Order By: Relevance
“…The majority of these studies focused on the small intestine, mainly the jejunum mucosa, with only a few evaluating the duodenum [30][31][32][33][34][35][36][37], despite its very high absorption potential [38]. In one case, supplementation with bamboo vinegar or polyunsaturated fatty acid from an extruded flax product resulted in a significant increase in duodenal villi height in aged hens, suggesting that diet composition affects the duodenal mucosal structure [29,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of these studies focused on the small intestine, mainly the jejunum mucosa, with only a few evaluating the duodenum [30][31][32][33][34][35][36][37], despite its very high absorption potential [38]. In one case, supplementation with bamboo vinegar or polyunsaturated fatty acid from an extruded flax product resulted in a significant increase in duodenal villi height in aged hens, suggesting that diet composition affects the duodenal mucosal structure [29,36].…”
Section: Discussionmentioning
confidence: 99%
“…In one case, supplementation with bamboo vinegar or polyunsaturated fatty acid from an extruded flax product resulted in a significant increase in duodenal villi height in aged hens, suggesting that diet composition affects the duodenal mucosal structure [29,36]. In another study, an increase in duodenal crypt depth was observed in 33-week-old hens supplemented with rapeseed expeller cake [34]. In these studies, changes induced by different substances on the intestinal mucosa were evaluated during the productive phase.…”
Section: Discussionmentioning
confidence: 99%
“…This beneficial effect could most likely be explained by the fact that supplementation of fermented feed may provide beneficial probiotic bacteria, such as lactic acid bacteria, and also prebiotic products produced during the pre-fermentation process [30,31]. Rapeseed meal has a relatively high fiber and anti-nutritional contents compared to soybean, which can potentially decrease growth performance in monogastric species [32]. However, the negative effects of these components may be removed by pre-fermentation of rapeseed meal so that nutrient digestibility of the product could be increased [33], while anti-nutritional factors such as tannin, phytate and glucosinolate could be degraded during the pre-fermentation process [13,31].…”
Section: Discussionmentioning
confidence: 99%
“…Los probióticos son aditivos alimentarios microbianos vivos que tienen un efecto beneficioso en el huésped al mejorar el equilibrio microbiano intestinal y mejorar el sistema inmunológico (9). Los prebióticos contienen componentes alimenticios no digeribles y aumentan el crecimiento o la actividad de especies bacterianas beneficiosas en el intestino y reducen la población de bacterias huésped dañinas (10). Los resultados de los estudios indican que la adición de prebióticos a la dieta no solo estimula el crecimiento y la actividad de las bacterias intestinales beneficiosas, sino que también puede aumentar el crecimiento y la actividad de las bacterias intestinales del huésped (10).…”
Section: Introductionunclassified
“…Los prebióticos contienen componentes alimenticios no digeribles y aumentan el crecimiento o la actividad de especies bacterianas beneficiosas en el intestino y reducen la población de bacterias huésped dañinas (10). Los resultados de los estudios indican que la adición de prebióticos a la dieta no solo estimula el crecimiento y la actividad de las bacterias intestinales beneficiosas, sino que también puede aumentar el crecimiento y la actividad de las bacterias intestinales del huésped (10). Por lo tanto, la investigación se ha centrado en otros aditivos para abordar las debilidades de los probióticos y prebióticos.…”
Section: Introductionunclassified